Artificial Intelligence In Education For Improving Student Learning Engagement In Higher Education - Sutrisno (CV. Gerasi Insan Nusantara, 2026)
The development of artificial intelligence (AI) has created significant changes in many sectors, including higher education. AI technologies enable new approaches in teaching and learning through personalized instruction, adaptive feedback, and interactive digital environments. This study examines the contribution of artificial intelligence to improving student learning engagement in higher education. The research applies a qualitative literature review method by examining recent academic publications related to AI integration in educational settings. The analysis indicates that AI supports student engagement through adaptive learning systems, intelligent tutoring systems, automated feedback, and learning analytics. These technologies assist students in accessing learning materials that match their learning pace and provide immediate responses to learning activities. AI-based platforms also create opportunities for interactive and collaborative learning. Several challenges remain related to ethical considerations, data privacy, technological infrastructure, and digital literacy within institutions. The study shows that artificial intelligence can strengthen student learning engagement when supported by effective pedagogical strategies and institutional readiness.